2007
DOI: 10.1101/gad.418707
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microRNAs are essential for mouse zygotic development

Abstract: MicroRNAs (miRNAs) have important roles in diverse cellular processes, but little is known about their identity and functions during early mammalian development. Here, we show the effects of the loss of maternal inheritance of miRNAs following specific deletion of Dicer from growing oocytes. The mutant mature oocytes were almost entirely depleted of all miRNAs, and they failed to progress through the first cell division, probably because of disorganized spindle formation. By comparing single-cell cDNA microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
583
2
15

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 524 publications
(628 citation statements)
references
References 31 publications
(27 reference statements)
28
583
2
15
Order By: Relevance
“…It was reported that miRNAs directly or indirectly control more than one third of the maternal genes expressed in oocytes [8]. High expressions of Dicer and miRNAs insured normal oocyte maturation and maintained meiotic spindle integrity which is necessary for normal meiotic maturation [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that miRNAs directly or indirectly control more than one third of the maternal genes expressed in oocytes [8]. High expressions of Dicer and miRNAs insured normal oocyte maturation and maintained meiotic spindle integrity which is necessary for normal meiotic maturation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, dynamic changes in miRNA expression during oogenesis have been found in growing mouse oocytes obtained from females 15-16 d after birth (postnatal days 15-16 [P15-P16]), at P20-P21, and mature oocytes from adult females [8]. Several miRNAs, such as miR-103, let-7 d, miR-16, miR-30b and miR-30c, were suggested to play fundamental roles in the meiosis of mouse GVoocytes [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations